Impact of COVID‐19 on family care partners of persons with dementia in long‐term care settings in Canada: Not a 'one‐size‐fits‐all' story. (December 2021) - McAiney, Carrie A; Boger, Jennifer; Conway, Emma; Koch, Melissa; Beleno, Ron; Boscart, Veronique; Dupuis, Kate; Dupuis, Sherry L; Keller, Heather; Kuepfer, Jane; Lee, Linda; Lopez, Kimberly; et al.
Abstract: Background: COVID‐19 has been devastating for older adults, particularly residents in long‐term care/retirement (LTC) homes. In an effort to curb the transmission of COVID‐19, public health measures have been put in place in many LTC homes, including mask wearing, physical distancing, and visitor restrictions. As the pandemic passes the one‐year mark, we are starting to understand the profound impacts of COVID‐19 and the corresponding public health measures on persons living with dementia (PLWD) and their family care partners (CPs). This research is part of a larger study exploring the impact of COVID‐19 on the wellbeing and social connections of PLWD and CPs. In this presentation, findings from qualitative interviews conducted with CPs of PLWD in LTC homes are shared. Methods: The overall study used an intrinsic case study design, involving survey and interview data. Following completion of a survey, participants were invited to participate in an in‐depth qualitative interview. Interviews were conducted by phone or online, transcribed verbatim, and analyzed using thematic analysis. Results: Eighteen CPs were interviewed. The impact of visitor restrictions varied between LTC homes and changed over the course of the pandemic, which was extremely challenging for CPs. At homes with visitor restrictions, the inability to visit family members with dementia was described as stressful, unfair, and frustrating. CPs stressed the importance of being able to visit their relatives, and ensuring their family members had regular social interaction to support their physical, social and emotional wellbeing. Even when CPs could visit, masks and physical distancing made communication with some PLWD challenging. Visitor policies also influenced perceptions of care. Some CPs felt that the needs of their family members with dementia were being met by the home, while others weren't sure because CPs weren't in the homes to assist staff and provide support to their family members with dementia. Conclusion: While COVID‐19 and the pandemic restrictions have been difficult for all CPs of persons with dementia in LTC, for some it has been agonizing. Understanding these varied experiences can help inform the development of individually‐tailored resources to better support the wellbeing of CPs.